A Convenient Method for Deoximation of Oximes by Using N-Iodosuccinimide Under Microwave Irradiation - Amini Manesh, Abbas; Khazaei, Ardeshir (Asian Journal of Chemistry, 2010)
A rapid and selective method for the cleavage of oximes has been achieved by a simple reaction of a ketoxime or an aldoxime with N-iodosuccinimide in acetone under microwave irradiations.